BLITAR COFFEE HUB: A COFFEE DISTRIBUTION AND EDUCATION CENTER WITH A BIOMORPHIC ARCHITECTURAL APPROACH - Putri Cahyani, Natasya; Winansih, Erna; Safrilia, Adisti (ARCHITENSA : Architectural Design Journal, 2025)
Blitar Coffee Hub is designed as a coffee distribution and education center that integrates economic, cultural, and community-based tourism functions. Originating from the significant potential of Arabica and Robusta coffee in Blitar, which has not been fully optimized in its distribution chain, this project provides an integrated hub that connects farmers, SMEs, tourists, and the community. The biomorphic architectural approach is applied to create organic spatial experiences inspired by natural forms, utilizing local materials such as bamboo, rattan, and wood as a manifestation of sustainability. The Coffee Hub is designed with three main functions: a post-harvest coffee distribution center, an educational facility that showcases the coffee journey from plantation to cup, and a tourism destination that also serves as an iconic architectural landmark of Blitar. Its presence is expected to strengthen Blitar’s identity as a coffee city, enhance the competitiveness of local SMEs, and create an inclusive and sustainable public space.